Integrating microfluidics and 3D bioprinting for advanced in vitro tissue and organ models - Fu, Wei; Shahariar Chowdhury,; Siew, Xian Chin; Yuan, Zhenya (Penerbit Universiti Kebangsaan Malaysia, 2025)
Advances in tissue engineering necessitate in vitro models that accurately replicate human organ complexity. The limitations of conventional 2D cultures and animal models have driven development of biomimetic platforms integrating microfluidics and 3D bioprinting. Microfluidic technologies enable precise control of fluid dynamics, nutrient delivery, and biochemical gradients at microscale, while 3D bioprinting facilitates layer-by-layer fabrication of complex tissue structures. This review examines design principles of microfluidic platforms, highlighting organ-on-a-chip and tumor-on-a-chip applications demonstrating controlled perfusion advantages. We analyze major bioprinting modalities, extrusion, inkjet, laser-assisted, and stereolithography, evaluating their suitability for specific tissue engineering applications. The review describes integration strategies, including direct cell bioprinting into microfluidic channels and using microfluidic molds for bioprinted constructs, which enhance vascularization and perfusion. We explore bioink advancements focusing on printability, mechanical properties, and stimulus-responsiveness (4D bioprinting). Finally, we address critical research directions: resolution enhancement, hierarchical vascular network development, AI-driven optimization, and regulatory standardization to facilitate clinical translation. This synthesis of current achievements and future directions aims to guide development of sophisticated in vitro models for disease modeling, drug discovery, and personalized medicine.